Eco-Literacy in ECE: A Case Study of Climate Change Awareness in Indonesia - Ira Anggraeni; Ajang Ramdani; Choirul Hidayah (EduBase : Journal of Basic Education, 2025)
Objective: This study analyzes the implementation of ecoliteracy-based climate change education in Early Childhood Education (PAUD) as a strategy to build environmental awareness and environmentally friendly behavior from an early age. Novelty: This study explores an approach that has not been widely explored that integrates the concept of sustainability into early childhood learning. Method: The study was conducted using a case study method in qualitative research. Data were collected through observation, teacher interviews, and document analysis. The ecoliteracy-based program involved activities such as gardening, recycling, and ecological storytelling. Results: The findings revealed that the majority of participants (85%) experienced developments in understanding the interconnectedness of ecosystems and awareness of nature protection. Through observation, positive behavioral changes were identified in children, such as increased discipline in sorting waste and active involvement in caring for plants. These changes indicate that the ecoliteracy approach has the potential to foster environmental awareness from an early age. Conclusion: This study offers new insights by positioning ecoliteracy as an alternative pedagogy for climate change education in PAUD. The findings show strong potential for integrating climate literacy into the PAUD curriculum and provide policy recommendations to support sustainable development through early childhood education.